Standardization of accounting and reporting: current state and ways of development - G. S. Dubrovina; Z. A. Andreeva (Путеводитель предпринимателя, 2020)
The principles of standardization of accounting and financial reporting in the context of different States. Resulting shown the impossibility of using data reporting documentation for comparison and economic analysis of foreign business partners in modern conditions of globalization of the market economy. The ways of development of standardization of modern accounting and reporting, aimed at integrating into the world community, through international financial reporting standards (IFRS).